On the Environmental Stress Cracking Resistance of High Density Polyethylene (HDPE) - Alsewailem, Fares D.; Alsaygh, Abdulhamid A.; Alqaflah, Abdulmajeed M. (Journal of Composites and Biodegradable Polymers, 2020)
This research reports a visualization investigation of environmental stress cracking (ESC) of a high-density polyethylene (HDPE) prepared in house and a commercial high-density polyethylene. The in house made HDPE showed an excellent resistance against ESC as none of the tested samples cracked under chemical solution and that was due to higher value of molecular weight and less percentage of chain branching. On the other hand, the commercial HDPE had poor resistance against ESC under chemical solution, as all tested samples was cracked and completely splitted up into two pieces. An interesting finding of this research was that the commercial HDPE of relatively lower molecular weight cracked when stressed within the environment of ordinary water. Finally, this research recommended a thorough investigation of the role of additives and fillers on the ESC resistant of Polyethylene.